Repositioning Implants Through Sandwich Osteotomy with the Interposition of Lyophilized Bovine Bone (International Journal of Medical and Surgical Sciences, 2015)
The satisfactory positioning of an implant during dental surgery is essential to the success of the treatment. However, accidents can occur during the period of osseointegration, leading to implant movements that hinder or may even prevent prosthetic rehabilitation. Implants can be repositioned through sandwich osteotomy, which has been labeled a versatile, viable and predictable technique in the literature. The aim of the present study was to report a case involving the esthetic displacement of an implant, caused by a sports accident, which was repositioned using sandwich osteotomy, with the interposition of lyophilized bovine bone between the osteotomized segments. In order to adequately perform this repositioning, the authors devised a guide to assist with the positioning process.
Keywords: Osteotomy; Dental implants; Biomaterials